Życzenia dla Jubilata - Koszko, Marta; Kowalewska, Kinga; Puppel, Joanna; Wąsikiewicz-Firlej, Emilia; Wilczyńska, Elwira (Scripta Neophilologica Posnaniensia, 2018)
Życzenia dla Jubilata: Profesora Stanisława Puppla